Sensitive Skin: Lessons From Transcriptomic Studies - Bataille, Adeline; Le Gall-Ianotto, Christelle; Genin, Emmanuelle; Misery, Laurent (Frontiers in Medicine, 2019)
In 2016, a special interest group from the International Forum for the Study of Itch defined sensitive skin (SS) as a syndrome that manifests with the occurrence of unpleasant sensations (stinging, burning, pain, pruritus, and tingling sensations) after stimuli that should not cause a reaction, such as water, cold, heat, or other physical and/or chemical factors. The pathophysiology of sensitive skin is still poorly understood, but the symptoms described suggest inflammation and peripheral innervation. Only two publications have focused on sensitive skin transcriptomics. In the first study, the authors performed a microarray comparison of SS and nonsensitive skin (NSS) samples and showed differences in the expression of numerous genes in SS and NSS samples. Moreover, in the SS samples, two clusters of genes were identified, including upregulated and downregulated genes, compared to NSS samples. These results provide some interesting clues for the understanding of the pathophysiology of SS. The second study compared SS and NSS samples using RNA-seq assays. This method allowed the identification of long noncoding RNAs (lncRNAs) and differentially expressed mRNAs and provided a comprehensive profile in subjects with SS. The results showed that a wide range of genes may be involved in the pathogenesis of SS and suggested pathways that could be associated with them. In this paper, we discuss these two studies in detail and show how transcriptomic studies can help understand the pathophysiology of sensitive skin. We call for new transcriptomic studies on larger populations to be conducted before putative pathogenic mechanisms can be detected and analyzed to achieve a better understanding of this complex condition..